Unilateral pleural effusion in chronic renal insufficiency: A clinician’s challenge - Sudhir Kumar Atri; Karthik Ambalavana; Anjali Dhanda; Shiv Kumar (Indian Journal of Case Reports, 2021)
Pleural effusion is a common clinical presentation of chronic kidney disease (CKD). Pleural effusion secondary to hypervolemia is usually bilateral in nature. We herein report a rare presentation of unilateral massive exudative pleural effusion in a 66-year-old male patient who is a known case of CKD, presented to us with severe dyspnea. On further evaluation, it was found that dyspnea was secondary to massive pleural effusion. After excluding other causes of pleural effusion, the patient was started on renal replacement therapy following which the patient improved markedly, and hence, pleural effusion was considered likely to be secondary to uremia. Uremia as such is a rare cause of pleural effusion and it should be considered as a diagnosis of exclusion.